Nilai Moral dalam Serat Panitibaya - Wijayanti, Anis; N., Yusro Edy; ., Hardyanto (Sutasoma : Jurnal Sastra Jawa, 2020)
ABSTRACT Panitibaya fiber is one of the piwulang Javanese texts that needs to be preserved because the teachings contained in it are still very beneficial for the community. For that Panitibaya Fiber will be examined on (1) how the sound layer in Panitibaya Fiber, (2) how the meaning layer in Panitibaya Fiber, (3) how the object layer in Panitbaya Fiber, (4) Moral Value in Panitibaya Fiber. This study uses a literary sociology approach according to Ian Watt. The research method used is descriptive qualitative. The data used in this study is the text of the Fiber Panitibaya written by Bathara Katong. Data collection techniques in this study were heuristic and hermeneutic reading methods. The analysis technique uses an analysis of the building blocks of poetry Roman Ingarden which includes sound layers, meaning layers, object layers. From the data, it was analyzed using Ian Watt's sociology theory of literature to find out the teachings contained in Panitibaya Fiber. The results of this study indicate that the existence of sound layers, layers of meaning and layers of objects, as well as moral values ​​contained in the Panitibaya Fiber for pursuing are summarized as eleven teachings as follows, (1) obligations to the Creator, (2) disgraceful qualities that must be shunned, (3) commendable traits, (4) actions that are not justified for men, (5) attitudes that must be considered in speech, (6) ancestral messages, (7) people who are not approachable, (8) actions related to children, (9) actions related to firearms, (10) there are visits and neighbors, and (11) attitude in handling a job. The teachings of the Panitibaya Fiber need to be disseminated in the Javanese community, either through print media or online media. Keywords: Panitibaya Fiber, Prohibition of pursuing life, Sociology of literature.